2000
DOI: 10.1021/om9906969
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformational Features of the Unsymmetrical Metalla Crown Ether cis-Mo(CO)4{2-(2,2‘-O2C12H8)PO(CH2CH2O)2- 2-C20H12-2‘-OP(2,2‘-O2C12H8)} from 2D NMR Spectroscopy and Molecular Modeling

Abstract: A new unsymmetrical metalla crown ether, cis-Mo(CO)4{2-(2,2‘-O2C12H8)PO(CH2CH2O)2-2-C20H12-2‘-OP(2,2‘-O2C12H8)}, has been designed for solution conformation studies. The complex was prepared by the reaction of the α,ω-bis(phosphorus donor) polyether ligand 2-(2,2‘-O2C12H8)PO(CH2CH2O)2-2-C20H12-2‘-OP(2,2‘-O2C12H8) with Mo(CO)4(nbd). Separate 1H NMR resonances were observed for six of the eight methylene protons of the metalla crown ether, indicating that the motion of the metalla crown ether ring was restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The 31 P{ 1 H} NMR resonance is a singlet. The chemical shift of the 31 P { 1 H} NMR resonance is close to those of other phosphite and bis(phosphite) ligands [2,32,33] derived from the 2,2 0 -biphenylylenephosphochloridite ester. The 1 H NMR spectrum of the ligand exhibits two resonances in the 4.09e4.30 ppm region, indicating that the protons attached to each methylene carbon are chemically equivalent.…”
Section: Hydroformylation Of Styrenesupporting
confidence: 51%
“…The 31 P{ 1 H} NMR resonance is a singlet. The chemical shift of the 31 P { 1 H} NMR resonance is close to those of other phosphite and bis(phosphite) ligands [2,32,33] derived from the 2,2 0 -biphenylylenephosphochloridite ester. The 1 H NMR spectrum of the ligand exhibits two resonances in the 4.09e4.30 ppm region, indicating that the protons attached to each methylene carbon are chemically equivalent.…”
Section: Hydroformylation Of Styrenesupporting
confidence: 51%
“…A number of ligands containing [1,3,2]dioxaphosphepin groups ( Figure ) derived from bis(aryl)diols such as 2,2‘-biphenol are currently used in asymmetric catalysis. Such ligands include symmetrical bis([1,3,2]dioxaphosphepin) ligands, asymmetrical bidentate phosphine−[1,3,2]dioxaphosphepin ligands, , and monodentate [1,3,2]dioxaphosphepin ligands . The axially chiral diaryl backbone in the [1,3,2]dioxaphosphepin groups should result in C 2 symmetry at the phosphorus; however, recent studies of ligands containing [1,3,2]dioxaphosphepin groups derived from 2,2‘-biphenol suggested that there is a low-energy pathway to inversion of the biphenyl group, even when the ligand is coordinated to an inert metal center .…”
Section: Introductionmentioning
confidence: 99%
“…These torsion angles are within the typical ranges observed for [Mo(CO) (6– n ) {P(X)(2,2′‐O 2 C 12 H 8 )} n ] complexes (O–P–O–C = |46.5 ± 7.1|°, P–O–C–C = |75.1 ± 3.9|°, ). Because the biphenyl groups of the [1,3,2]‐dioxaphosphepin rings racemize in solution, their complexes often crystallize in centrosymmetric space groups with both enantiomers in the same crystal as do 6 ( P 2 1 / c ) and 7 ( P 2 1 / n ) , , , . However, enantiomers can also segregate upon crystallization into a noncentrosymmetric space groups as does 3 , …”
Section: Resultsmentioning
confidence: 99%